High School Students Residing in Educational Public Institutions: Health-Risk Behaviors. - Priscilla Rayanne E Silva Noll; Nusa de Almeida Silveira; Matias Noll; Patrícia de Sá Barros (PLoS ONE, 2016)
Although several health-risk behaviors of adolescents have been described in the literature, data of high school students who reside at educational institutions in developing countries are scarce. This study aimed to describe behaviors associated with health risks among high school students who reside at an educational public institution and to associate these variables with the length of stay at the institution. This cross-sectional study was conducted during the year 2015 and included 122 students aged 14-19 years at a federal educational institution in the Midwest of Brazil; students were divided into residents of <8 months and those of >20 months. Information concerning the family socioeconomic status and anthropometric, dietary and behavioral profiles was investigated. Despite being physically active, students exhibited risk-associated behaviors such as cigarette and alcohol use and risky sexual behaviors that were exacerbated by fragile socioeconomic conditions and distance from family. A longer time in residence at the institution was associated with an older age (p ≤ 0.001), adequate body mass index (BMI; p = 0.02), nutritional knowledge (p = 0.01), and less doses of alcohol consumption (p ≤ 0.01) compared with those with shorter times in residence. In conclusion, the students exhibited different health-risk behaviors, and a longer institutional residence time, compared with a shorter time, was found to associate with the reduction of health-risk behaviors.